1996
DOI: 10.1046/j.1365-2133.1996.d01-1096.x
|View full text |Cite
|
Sign up to set email alerts
|

Angry back syndrome': a non-reproducible phenomenon

Abstract: The term 'angry back syndrome' (ABS) was coined by Mitchell in 1975. It was stated that a strong positive patch test reaction could create an 'angry back' which becomes hyper-reactive to other patch test challenges. The present study investigated whether the ABS is a generalized state of hyper-reactivity of skin, whether it is a localized hyper-reactivity of skin, i.e. only in the close proximity to a strong patch test reaction, whether it is an individual specific phenomenon and if ABS is a reproducible pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 14 publications
0
21
1
Order By: Relevance
“…Another study found that an extreme patch test reaction to fragrance mix I was associated with additional positive reactions . A possible explanation for our findings could be the often mentioned ‘angry back syndrome’, or ‘excited skin syndrome’, although the actual existence of these phenomena has been disputed, and the occurrence is thought to be rare at best . The best explanation for more strong/extreme positive reactions in polysensitized individuals would be that polysensitization is a sign of heightened susceptibility, which is also expressed by increased reactivity.…”
Section: Discussionmentioning
confidence: 68%
“…Another study found that an extreme patch test reaction to fragrance mix I was associated with additional positive reactions . A possible explanation for our findings could be the often mentioned ‘angry back syndrome’, or ‘excited skin syndrome’, although the actual existence of these phenomena has been disputed, and the occurrence is thought to be rare at best . The best explanation for more strong/extreme positive reactions in polysensitized individuals would be that polysensitization is a sign of heightened susceptibility, which is also expressed by increased reactivity.…”
Section: Discussionmentioning
confidence: 68%
“…This involved the topical application of a dose series of CO on individual patches comprising 8-mm aluminum Finn chambers mounted on hypoallergenic scanpor tape and 7-mm filter paper discs. Patches were applied in duplicate to the inner aspect of the upper arm in the following concentrations: 10 KL of CO in 0.3%, 0.55%, 1.0%, and 3% ethanol; and 10 KL of 100% ethanol control patch (23). To account for local anatomical variability, the location of each concentration was randomized.…”
Section: The Effect Of Prolonged Moderate-intensity Exercise On the Cmentioning
confidence: 99%
“…To account for local anatomical variability, the location of each concentration was randomized. Patches remained in place for exactly 24 h, and the assessment of cutaneous responses was performed 2 h after removal of the CO patches, as described (23).…”
Section: The Effect Of Prolonged Moderate-intensity Exercise On the Cmentioning
confidence: 99%
“…From classic contact patch testing, it is well known that reproducibility decreases as more positive reactions occur simultaneously in the first test, when a patient is tested in close proximity to another positive allergic reaction, and when a strong irritant is included in the test series 25,26 . These conditions induce a general state of hyperreactivity called “angry back syndrome” (excited skin syndrome) 25–28 . It is difficult to explain why we observed different proportions of the two types of nonreproducible positive APT result (positive becoming negative and negative becoming positive) across our three groups.…”
Section: Discussionmentioning
confidence: 76%